2022
DOI: 10.5114/ada.2022.113827
|View full text |Cite
|
Sign up to set email alerts
|

Great hopes or disappointment – a survey-based study on patients’ and doctors’ perception of telemedicine during the COVID-19 pandemic in Poland

Abstract: Introduction: During the COVID-19 pandemic health care systems worldwide rapidly implemented telemedicine solutions in order to avoid spreading the coronavirus among doctors and patients. Aim: To analyse the knowledge, usage, and attitude towards telemedicine among patients, dermatologists, and other doctors during the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although this form of visit gained importance during the pandemic because it was easily accessible for most patients, its quality was not always satisfactory. In addition to teleconsultation, telemonitoring of patients after myocardial infarction has developed, including e-oximeter, allowing for monitoring of heart rhythm and blood saturation [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Although this form of visit gained importance during the pandemic because it was easily accessible for most patients, its quality was not always satisfactory. In addition to teleconsultation, telemonitoring of patients after myocardial infarction has developed, including e-oximeter, allowing for monitoring of heart rhythm and blood saturation [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, a survey during the first year of the COVID-19 pandemic revealed a similar reluctance from patients, who doubted telemedicine’s effectiveness in adequately assessing skin lesions. This scepticism was underscored by the fact that 96.6% of dermatologists needed additional in-office visits or extra pictures due to unclear clinical images [ 87 ]. Another study during the pandemic on the Polish population echoed these concerns, noting the fear of missing serious illnesses without direct contact.…”
Section: Telemedicine and Stis Amid The Covid-19 Global Epidemicmentioning
confidence: 99%
“…A similar trend in TC uptake has also been observed in other countries, including Australia, Canada, and the United States [ 40 , 41 , 42 ]. In August 2020, a study of Polish patients found half to be satisfied with TCs [ 39 ]; however, later studies revealed more negative attitudes, particularly among those with chronic diseases or experiencing emergencies, who complained that TCs were replacing visits instead of supplementing them [ 43 , 44 ]. However, the preferences and experiences of Polish PwDs in this context remain unstudied.…”
Section: Introductionmentioning
confidence: 99%